PENGARUH CYBERFEMINISM MELALUI ARTIKEL MEDIA ONLINE MAGDALENE TERHADAP PENINGKATAN KESADARAN GENERASI Z MENGENAI KEKERASAN BERBASIS GENDER ONLINE (KBGO) - Saskia Amalia Rosyananda (2022)
The issue of OGBV requires public awareness and attention due to the stigma that is still circulating. The intensity of internet usage and high awareness in Generation Z can help overcome OGBV. This study aims to determine how much influence cyberfeminism online media articles have on increasing awareness of Generation Z on the issue of OGBV using the Media Ecology theory by Marshall McLuhan which has the assumption that the media is able to influence society, organize experiences and unite the whole world. This research uses positivism paradigm and is an explanative quantitative research. Researchers used a quantitative approach and survey methods. The data analysis technique used is validity test, reliability test, correlation test, simple linear regression analysis and t test. The final result of this study shows that cyberfeminism in online media article has a great influence on increasing awareness of Generation Z on the issue of OGBV. The results of the correlation test obtained a percentage of 61.30%. The regression analysis test showed the results of Y = 13,318 + 0.656X with a coefficient of 0.656 and a positive value. The researcher obtained the results of the t test which showed the results of the calculation of t count 12,569 > t table 1,290. This means that H0 is rejected and H1 is accepted. Researchers can conclude that there is a big influence between cyberfeminism media articles online on increasing awareness of Generation Z on the issue of OBGV.